Phosphotidylserine exposure and neutrophil extracellular traps enhance procoagulant activity in patients with inflammatory bowel disease - He, Zhangxiu; Si, Yu; Jiang, Tao; Ma, Ruishuang; Zhang, Yan; Cao, Muhua; Li, Tao; Yao, Zhipeng; Zhao, Lu; Fang, Shaohong; Yu, Bo; Dong, Zengxiang; Thatte, Hemant S.; Bi, Yayan; Kou, Junjie; Yang, Shufen; Piao, Daxun; Hao, Lirong; Zhou, Jin; Shi, Jialan (Thrombosis and Haemostasis, 2016)
Inflammatory bowel disease (IBD)-associated thromboembolic event often lacks precise aetiology. The aim of this study was to investigate the contribution of phosphatidylserine (PS) exposure and neutrophil extracellular traps (NETs) towards the hypercoagulable state in IBD. We demonstrated that the levels of PS exposed MPs and the sources of MP-origin, platelets, erythrocytes, leukocytes and cultured endothelial cells (ECs) were higher in IBD groups than in healthy controls using flow cytometry and confocal microscopy. Wright-Giemsa and immunofluorescence staining demonstrated that the elevated NETs were released by activated IBD neutrophils or by control neutrophils treated with IBD sera obtained from patients with the active disease. MPs and MP-origin cells in IBD groups, especially in active stage, markedly shortened coagulation time and had increased levels of fibrin, thrombin and FXa production as assessed by coagulation function assays. Importantly, we found that on stimulated ECs, PS rich membranes provided binding sites for FXa and FVa, promoting fibrin formation while TNF blockage or IgG depletion attenuated this effect. Treatment of control neutrophils with TNF and isolated IgG from PR3-ANCA-positive active IBD patients also resulted in the release of NETs. Blockade of PS with lactadherin prolonged coagulation time, decreased fibrin formation to control levels, and inhibited the procoagulant enzymes production in the MPs and MP-origin cells. NET cleavage by DNase I partly decreased PCA in IBD or stimulated neutrophils. Our study reveals a previously unrecognised link between hypercoagulable state and PS exposure or NETs, and may further explain the epidemiological association of thrombosis within IBD patients.
Keywords: IBD hypercoagulable disorders; phosphatidylserine; Neutrophil Extracellular Traps; procoagulant activity